StarBRITE: The Vanderbilt University Biomedical Research Integration, Translation and Education Portal - Harris, Paul A. (2011)
StarBRITE is a one-stop, web-based research portal designed to meet the day-to-day needs of the Vanderbilt University and Meharry Medical College research community during the planning and conduct of research studies. StarBRITE serves as the main online location for research support addressing issues such as identification and location of resources, identification of experts, guidance for regulatory applications and approvals, regulatory assistance, funding requests, research data planning and collection, and serves as a central repository for educational offerings. To date, there have been more than 590,038 StarBRITE hits by more than 6582 cumulative users. We present here StarBRITE design objectives, details about technical infrastructure and system components, status report and activity metrics for the first 2.75-years of operation, and a report of lessons learned during organizing, launching and refining the portal.